Lightweight network-coded ARQ: An approach for Ultra-Reliable Low Latency Communication - Karetsi, Foteini; Papapetrou, Evangelos (Computer communications, 2022)
Sliding Window RLNC schemes represent a novel, promising and efficient class of algorithms for reliable data transmission over an unreliable link. They combine Random Linear Network Coding (RLNC) with the idea of sliding window from (Automatic Repeat reQuest) ARQ protocols in order to help the basic ARQ mechanism to quickly recover from losses through redundant coded packets. Although very successful, we make the observation that such schemes bear significant limitations stemming from the fact that both the ARQ mechanism and the coding process operate on the same group of packets, called the sliding window. To tackle the problem, we propose the use of two distinct windows; the sliding window, which can be used to optimize the data flow based on the link’s bandwidth-delay product, and the coding window that can be used exclusively in the coding process. We analyze the performance of the proposed strategy and show that it provides an improved coding operation while at the same time reduces the coding complexity. Then, we delineate rapidARQ, a sliding window RLNC protocol that adopts the proposed strategy, and experimentally confirm that it outperforms other state-of-the-art sliding window RLNC schemes. More specifically, it achieves superior throughput-delay performance that better fits in the context of Ultra-Reliable Low-Latency Communication (URLLC) while at the same time it significantly reduces the coding complexity. Moreover, we show that the superior performance of rapidARQ is more prominent in channels with large bandwidth-delay products, a fact that renders its utility to current and future networks more essential.